Sustainability Capacity of HIV Programs in National Capital Region, Philippines - Euris John B. Cawaling; Dennise U. Cunanan; Racidon P. Bernarte (International Journal of Public Health Science (IJPHS), 2018)
Across all the regions in the Philippines, the National Capital Region (NCR) got the highest percentage (37%) for HIV newly diagnosed cases based from  the July-August 2017 HIV/AIDS and ART Registry of the Philippines’ report. The National HIV, AIDS, and STI Prevention and Control Program (NASPCP) of the Department of Health (DOH) lead the different health services in the prevention of HIV transmission. Anchored with the NASPCP, different HIV programs of DOH’s selected partner institutions and organizations within NCR continuously exist. However, due to the increase on the number of newly diagnosed HIV cases in the country, ensuring its sustainability through assessing the different domains of their program was in need to be studied. This article was based from an undergraduate thesis study which aimed to assess the sustainability capacity of HIV programs among DOH’s selected partner institutions and organizations within NCR, Philippines, scoping the eight domains specifically the environmental support, funding stability, partnerships, organizational capacity, program evaluation, program adaptation, communications, and strategic planning. The study used a quantitative approach; 17 government institutions specifically city health offices and 13 non-government HIV-related organizations for a total of 30 respondents. Survey method was utilized using the standardized Program Sustainability Assessment Tool adapted from the Washington University in St. Louis. Based from the results and findings of the study, generally, all the domains were leaning either in great and greater extent as verbally interpreted. From the conclusion, all the domains of the HIV programs of the respondents were sustainable. However, the study recommended to the DOH and all the HIV program implementers the developed and proposed narrative-type action plan. By that means, future researchers can assess again and see if the NCR achieved the vision of the Health Sector Plan for HIV and STI for the year 2015-2020 to have zero new infections, zero discrimination, and zero AIDS-related deaths.